Synthesis of Purine‐based Triazoles by Copper (I)‐catalyzed Huisgen Azide–Alkyne Cycloaddition Reaction. (13th October 2017) - Kapadiya, Khushal; Jadeja, Yashwantsinh; Khunt, Ranjan
Abstract : An efficient protocol for the synthesis of substituted 1, 2, 3‐triazol‐9 H ‐purines via copper (I)‐catalyzed click chemistry of 2, 6‐dichloropurine with aromatic azide has been reported. A wide range of 1, 4‐disubstituted triazoles ( N ‐9 substituted purines) was accessible in good‐to‐excellent yields with remarkable functional group tolerance. The base‐catalyst ratio was tuned to achieve optimum reaction condition (>95% conversion and purity in most cases). Furthermore, the structure of4i has been unambiguously assigned by X‐ray crystallographic study to yield structural information on the 1, 3‐dipoles entering the reaction. Abstract :